Re-Visioning Arts and Cultural Policy: Current Impasses and Future Directions - Craik, Jennifer (ANU Press, 2007)
In this monograph, Jennifer Craik undertakes a critical and historical analysis of the main imperatives of arts and cultural policy in Australia. With forensic skill she examines the financial and policy instruments commonly relied upon in this much contested and diverse area of public policy. Craik uses her analysis of past and current policy responses as a platform for articulating future options. This is a valuable work for cultural professionals and administrators, art historians and, indeed, anyone with an abiding interest in the management of the nation's cultural estate.